Nurses’ strategies for coping with stress in the face of the influx of war refugees from Ukraine to Poland - Kowalczuk, Krystyna; Tomaszewska, Katarzyna; Szpakow, Andriej; Krajewska-Kułak, Elżbieta; Sobolewski, Marek; Hermanowicz, Justyna Magdalena (Frontiers in Psychiatry, 2024)
Introduction: Russian military's incursion into Ukraine sparked the largest refugee crisis in Europe since World War II. As Ukraine's neighboring country, Poland became the primary destination for these refugees. Ukrainians staying in Poland under the EU's Temporary Protection Directive receive humanitarian support similarly to asylum seekers, but the legal pathways, length of stay and integration processes differ significantly as the Directive provides for more immediate, collective protection without the complexity of individual asylum applications. The influx of war refugees generates extremely complex situations that health personnel, especially nurses, must face on a daily basis. Aim: Identify whether and to what extent the emergence of a large number of patients with war-related experiences constituted a source of stress for nurses, and how Polish nurses coped with this issue. Materials and method: A cross-sectional study was conducted in December 2022 in Białystok, Poland. It included 473 certified nurses working in hospitals affiliated with the District Chamber of Nurses in Białystok. Perceived Stress Scale (PSS-10) questionnaire and Mini-COPE inventory (Polish version of Carver'a BriefCOPE inventory were used in the study.Results: The average stress level among nurses was moderate, with nearly equal proportions of nurses experiencing low, medium, and high stress levels. Nurses who had contact with refugees in the last six months and/or helped them, did not present an increased level of stress -on the contrary, this level was lower. Nurses who helped refugees at work more often used a planning strategy in stressful situations, and less frequently reacted to stress using humour, religion, denial or venting. Conclusions: The greater workload and more frequent contacts between Polish nurses and Ukrainian war refugees were a factor increasing work fatigue, but, paradoxically, at the same time reducing the level of stress in a situation giving the feeling of a duty well fulfilled. Empowering nurses through greater autonomy and fostering supportive work environments, especially in crisis situations like the care of war refugees has a positive impact on coping with stress.